POLITICAL ELITES AND A POLITY IN THE MAKING: THE CASE OF EU - M. Cotta (Сравнительная политика, 2015)
This paper is devoted to an exploration of some aspects of this relationship through an analysis of the process of European integration. By analyzing the institutional transformation brought about by the Lisbon treaty, the attitudes of national elites toward the European form of government, and the impact of the recent crisis on the European institutions, the article tries to establish the role of elites in the development of a supranational polity, and to ascertain what influence institutional transformations have had on the formation of a genuinely European elite.